Digital transformation of enterprises: Job creation or job destruction? - Huang, Yuhong (Technological forecasting & social change, 2024)
In recent years, the technological advancements embodied by digital technology have received significant attention from policymakers and researchers because of their profound impacts on the economy and society. In particular, the relationship between digital technology and employment continues to be a subject of considerable debate. This article focuses on the microperspective, and the causal effects and mechanisms of corporate digital transformation on labour employment are examined. With the use of data on Chinese A-share manufacturing companies from 2008– to 2019, text analysis is employed in this study to construct a comprehensive index of corporate digital transformation. We utilise a combination of fixed effects models, difference-in-differences (DiD) models, and instrumental variable methods and demonstrate that digital transformation stimulates enterprise labour demand, a conclusion that remains valid after multiple endogeneity tests and robustness assessments. The heterogeneous results indicate that nonstate-owned enterprises (non-SOEs), nonhigh-tech enterprises, enterprises with low financing constraints, and small enterprises exhibit greater employment creation effects through digital transformation. Mechanistic analysis suggests that digital transformation increases enterprise employment by increasing operational and management efficiency, profitability, and labour productivity levels. Further exploration reveals that digital transformation increases the demand for labour with varying skills and human capital upgrading in enterprises. This article, through the lens of digital technology, enriches the body of research on the nexus between technological progress and employment, provides novel insights into employment fluctuations under the digital paradigm, and outlines significant implications for countries balancing digital economy development, employment growth, and social stability. •The digital transformation of enterprises has a job-creating effect on employment and promotes employment stability.•Reduces operational costs, enhances profitability, and boosts labour productivity are the primary channels of effect.•The use of digital technology in China's manufacturing sector has facilitated the upgrading of companies' human capital.•The employment creation effect of corporate digital transformation exhibits asymmetry across different types of enterprises.